Ictiofauna associada a recifes naturais e artificais em uma reserva extrativista marinha - Martins, Francisco Allan Santos (2019)
Natural reefs, whether of biological origin or not, notably contain a rich and established ichthyofauna, including many species of interest for commercial fishing. Similarly, but of unnatural origin, artificial marine reefs are used to increase fish productivity and provide additional habitats to the ecosystem. Stationary visual censuses were carried out on natural and artificial reefs present at the RESEX Prainha do Canto Verde Extractive Reserve (Beberibe-CE, Brazil) in order to evaluate the structure of the assemblage and to inventory and compare the ichthyofauna between reef types. The substrate was also evaluated qualitatively through photo-quadrats to record the benthic community. A significant difference was observed between the assemblages of the reef types studied. The nMDS shows a segregation between samples that represent an artificial reef closer to the coast and a more distant natural reef, probably due to the abundance recorded at each of these points. Both the natural and artificial reefs presented greater abundances of fish of length <20cm, however, fishes at the artificial reefs were observed distributed in classes of length >40cm. Trophic categories did not differ between natural and artificial reefs; however, they were statistically different when compared within each type of reef. Of the species considered targets at the Extractive Reserve, only one was not observed during the censuses (Scomberomorus cavalla); however, only the species Ocyurus chrysurus was considered abundant and common in the natural reefs. Macroalgae dominated the substrates of the natural reefs, while sand and gravel constituted the substrate where the artificial reefs are located, with the presence of benthic species adhering to the structures. Artificial reefs contribute in a general way to the aggregation of prey for the target species, favoring fish productivity. However, the conservation of adjacent natural environments and measures to assess the impact of the use of artificial structures in protected areas are necessary to guarantee the sustainability of the initiative with respect to fishery production.